A diaphragm, its method of manufacture and use

CN122968592APending Publication Date: 2026-10-23JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611176934.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,这类材料存在以下缺陷:炭黑等材料在高温下可能被电解液润湿溶胀,PTC效应可逆或失效;且其化学稳定性一般,可能与电解液发生副反应;仅依靠电阻变化来关断,在极端热滥用情况下,物理隔膜的闭孔温度可能滞后于电学关断,导致热失控无法被完全抑制

Benefits of technology

本发明隔膜的涂层中包含金属掺杂二氧化钒纳米线,金属掺杂二氧化钒纳米线包覆有第一包覆层,第一包覆层材料选自六方氮化硼、氧化铝、二氧化硅中的至少一种。本发明的隔膜涂层在二氧化钒(VO2)发生相变后(60-70℃),处于金属相的VO2表面对Li+具有异常的吸附与俘获效应。此时,作为界面调控层的第一包覆层与金属态VO2构成一个独特的“离子俘获界面”,第一包覆层通过其原子空位缺陷产生的局域电场效应和化学吸附位点,能够强力捕获试图穿越的Li+,使其被“固定”在VO2表面,形成动态的离子迁移壁垒,极大地增加了锂离子跨隔膜传输的难度,金属相VO2表面产生对Li+的化学吸附效应,同时第一包覆层晶格结构变化增大Li+扩散势垒,协同阻断锂离子跨隔膜传输,使电池内部电化学反应速率急剧下降,从而在热失控发生前主动降低电池功率输出,实现离子级关断保护。"

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a diaphragm, which comprises a base film and a coating layer arranged on at least one surface of the base film, wherein the coating layer comprises metal-doped vanadium dioxide nanowires with a chemical formula of M x V 1‑x O2, wherein x is 0.03-0.05, M is at least one selected from tungsten, molybdenum and niobium, and at least part of the surface of the metal-doped vanadium dioxide nanowires is coated with a first coating layer, and the material of the first coating layer is at least one selected from hexagonal boron nitride, aluminum oxide and silicon dioxide. The diaphragm can effectively avoid thermal runaway of lithium ions and provide safety far beyond a single mechanism (such as traditional PTC or simple closed pores).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, and in particular to a separator, its preparation method and application. Background Technology

[0002] With the growing global demand for clean energy and sustainable development, lithium-ion batteries, thanks to their high energy density and stable cycle performance, have found increasingly widespread applications in mobile electronic devices, electric vehicles, and large-scale energy storage. However, thermal runaway is a core safety concern for lithium-ion batteries. When the internal temperature of the battery rises abnormally, if the electrochemical reaction is not stopped in time, it will lead to a chain reaction of exothermic heat, causing a fire or explosion.

[0003] In existing technologies, coating a membrane with PTC material is a common thermal shutdown strategy. Traditional PTC materials are mostly composites of conductive fillers (such as carbon black and carbon nanotubes) and polymers. When the temperature rises, the polymer matrix expands, disrupting the conductive network and causing a sharp increase in resistance, thereby cutting off the current. However, these materials have the following drawbacks: materials such as carbon black may be wetted and swollen by the electrolyte at high temperatures, making the PTC effect reversible or ineffective; their chemical stability is generally poor, and they may undergo side reactions with the electrolyte; relying solely on resistance changes for shutdown may lead to a lag in the pore-closing temperature of the physical membrane compared to electrical shutdown under extreme thermal abuse conditions, resulting in thermal runaway not being completely suppressed. Therefore, developing a novel smart membrane based on unconventional materials with multiple synergistic protection mechanisms is of great significance. Summary of the Invention

[0004] The purpose of this invention is to provide a separator, its preparation method and application, which can effectively prevent the thermal runaway of lithium ions and provide safety far exceeding that of a single mechanism (such as traditional PTC or simple closed-cell membrane).

[0005] For the purposes of this invention, the following technical solution is adopted: On one hand, the present invention provides a diaphragm, the diaphragm comprising: A base film and a coating disposed on at least one surface of the base film, the coating comprising: Metal-doped vanadium dioxide nanowires, wherein the chemical formula of the metal-doped vanadium dioxide nanowires is M x V 1-x O2, wherein x is 0.03-0.05; M is selected from at least one of tungsten, molybdenum and niobium; at least a portion of the surface of the metal-doped vanadium dioxide nanowire is further coated with a first coating layer, the first coating layer material being selected from at least one of hexagonal boron nitride, alumina and silicon dioxide.

[0006] In an embodiment of the present invention, at least a portion of the surface of the first coating layer is coated with a second coating layer, wherein the material of the second coating layer is polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether).

[0007] In an embodiment of the present invention, the aspect ratio of the metal-doped vanadium dioxide nanowire is (50-200):1.

[0008] In an embodiment of the present invention, the thickness of the first coating layer is 2-5 nm; the thickness of the second coating layer is 2-5 nm.

[0009] In an embodiment of the present invention, the thickness of the diaphragm coating is 2-6 μm.

[0010] In an embodiment of the present invention, the base film is a polyolefin film with a thickness of 5-8 μm.

[0011] On the other hand, the present invention also provides a method for preparing a diaphragm, comprising the following steps: S1. Mix the metal source, vanadium source, and reducing agent, then carry out a hydrothermal reaction. After washing and drying, calcinate to obtain the chemical formula M. x V 1-x Metal-doped vanadium dioxide nanowires of O2, wherein x is 0.03-0.05 and M is selected from at least one of tungsten, molybdenum and niobium; A first coating layer material is deposited on the surface of the metal-doped vanadium dioxide nanowire to obtain metal-doped vanadium dioxide nanowire with the first coating layer; the first coating layer material is selected from at least one of hexagonal boron nitride, aluminum oxide, and silicon dioxide. S2. PEO-thiocarbonate is pre-activated with an initiator, and then hydrothermally reacted with VBGE monomer to obtain poly(4-vinylbenzyl glycidyl ether). S3. Mix the metal-doped vanadium dioxide nanowires with the first coating layer obtained in step S1 with the polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether) obtained in step S2 to form a slurry. Coat the slurry on at least one surface of the base membrane to obtain the composite membrane. The execution order of steps S1 and S2 is not important.

[0012] In an embodiment of the present invention, step S1 satisfies at least one of the following features: (1) The vanadium source includes at least one of ammonium metavanadate, vanadium pentoxide, sodium vanadate, vanadium trichloride, and vanadium oxysulfate; (2) The metal source is a tungsten source, and the tungsten source includes at least one of ammonium metatungstate, ammonium paratungstate, sodium tungstate, and potassium tungstate; (3) The reducing agent includes at least one of oxalic acid, urea, ascorbic acid, and hydrazine hydrate; (4) The molar ratio of the metal source and the vanadium source satisfies the following: the molar ratio of the metal element to the vanadium element is (3-5):100; (5) The molar ratio of the reducing agent to the vanadium element in the vanadium source is (1.5-2.5):1; (6) In step S1, the hydrothermal reaction specifically refers to a reaction time of 48-72 hours at 180-240℃; (7) The calcination specifically involves heating to 500-600°C at a rate of 2-5°C / min under an inert atmosphere and holding at that temperature for 2-4 hours.

[0013] (8) The first coating material is hexagonal boron nitride, and the mass ratio of the first coating to the metal-doped vanadium dioxide nanowire is (5-30):(70-95). (9) The temperature of the atomic layer deposition is 150-200℃ and the number of atomic layer deposition cycles is 40-100.

[0014] In an embodiment of the present invention, step S2 satisfies at least one of the following features: (1) The pre-activation reaction refers to stirring the reaction at 70-100℃ for 6-10 hours; (2) The initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide; (3) The molar ratio of the PEO-thiocarbonate to the initiator is 1:(0.15-0.25). (4) The molar ratio of the PEO-thiocarbonate to the VBGE monomer is 1:50 - 1:100; (5) In step S2, the hydrothermal reaction is specifically carried out at 60-100°C for 18-36 hours under an inert atmosphere.

[0015] In an embodiment of the present invention, in step S3, the mass ratio of the metal-doped vanadium dioxide nanowire with the first coating layer to the poly(4-vinylbenzyl glycidyl ether) is (70~90): 20.

[0016] In this embodiment of the invention, the mixing specifically involves stirring at a speed of 1500-2500 rpm for 1.5-2.5 hours, followed by ultrasonic treatment for 25-35 minutes.

[0017] In another aspect, the present invention also provides a lithium-ion battery comprising the separator as described above; and / or a separator prepared according to the separator preparation method described above.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The membrane coating of this invention comprises metal-doped vanadium dioxide nanowires, which are coated with a first coating layer. The first coating layer material is selected from at least one of hexagonal boron nitride, alumina, and silicon dioxide. After the vanadium dioxide (VO2) undergoes a phase transition (60-70℃), the VO2 surface in the metallic phase of the membrane coating of this invention reacts with Li... + It exhibits unusual adsorption and trapping effects. At this point, the first coating layer, acting as the interface control layer, forms a unique "ion trapping interface" with metallic VO2. The first coating layer, through the localized electric field effect generated by its atomic vacancy defects and chemisorption sites, can strongly trap Li attempting to cross it. + This "fixes" the lithium ions onto the VO2 surface, forming a dynamic ion migration barrier that significantly increases the difficulty of lithium ion transport across the membrane. The metallic VO2 surface also generates a barrier against the lithium ions. + The chemical adsorption effect, and the change in the lattice structure of the first coating layer increases the Li + The diffusion barrier synergistically blocks lithium-ion transport across the separator, causing a sharp decrease in the rate of electrochemical reactions inside the battery. This proactively reduces the battery power output before thermal runaway occurs, achieving ion-level shutdown protection. The first coating layer of the separator of this invention not only isolates VO2 from direct contact with the electrolyte to prevent side reactions, but is also an excellent electronic insulator. Through a dual strategy of "electron discharge (VO2-based composite material used for the separator coating) + ion blocking," the separator of this invention ensures that the battery can be rapidly, completely, and permanently "shut down" in the early stages of thermal runaway, providing safety far exceeding that of a single mechanism (such as traditional PTC or simple pore blocking).

[0019] The separator of this invention may further include a second coating layer, the second coating layer material being polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether), which can provide ionic conductivity and mechanical toughness at room temperature. The epoxy groups of the poly(4-vinylbenzyl glycidyl ether) block side chains are stable at room temperature, but under thermal abuse conditions (100°C and above), they can undergo a rapid ring-opening-fluorination-crosslinking synergistic reaction with HF generated from the decomposition of LiPF6, causing the polymer coating to undergo a violent and irreversible volume expansion (up to 300%-500% of the original volume) in a short time, completely blocking the micropores of the base membrane and the pores of the coating itself like a "cork," thereby achieving ion thermal cutoff of the lithium battery. Detailed Implementation

[0020] To better understand and implement this application, the technical solutions of this application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only some of the embodiments of this application, and not all of them.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.

[0022] Unless otherwise stated, all numerical values ​​for the amounts of expressed components, reaction conditions, etc., used in the specification and claims are to be understood as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values ​​that can be varied to obtain the desired performance.

[0023] For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0024] The word “and / or” as used in this article refers to one or all of the elements mentioned.

[0025] The terms "include" and "contain" as used in this article cover both cases where only the mentioned elements exist and cases where other unmentioned elements exist in addition to the mentioned elements.

[0026] To overcome the bottlenecks of existing technologies, this invention proposes for the first time the use of specially designed and stabilized VO2-based composite materials for membrane coatings. By utilizing its keen phase change characteristics and cleverly designing its synergistic ionic effect with polymer materials and electrolytes, a dual, irreversible thermal shutdown mechanism that is triggered at a relatively low temperature (60~70℃) and combines electron blocking and ion blocking is achieved, effectively avoiding lithium-ion thermal runaway. The following is a detailed description of this application.

[0027] diaphragm On one hand, the present invention provides a diaphragm, the diaphragm comprising: A base film and a coating disposed on at least one surface of the base film, the coating comprising: Metal-doped vanadium dioxide nanowires, wherein the chemical formula of the metal-doped vanadium dioxide nanowires is M x V 1-xO2, wherein x is 0.03-0.05; M is selected from at least one of tungsten, molybdenum and niobium; at least a portion of the surface of the metal-doped vanadium dioxide nanowire is further coated with a first coating layer, the first coating layer material being selected from at least one of hexagonal boron nitride, alumina and silicon dioxide.

[0028] In the above technical solution, the membrane coating includes metal-doped vanadium dioxide nanowires, which are coated with a first coating layer. The first coating layer material is selected from at least one of hexagonal boron nitride, alumina, and silicon dioxide. After the vanadium dioxide (VO2) undergoes a phase transition (65°C), the VO2 surface in the metallic phase reacts with Li... + It exhibits unusual adsorption and trapping effects. At this point, the first coating layer, acting as the interface control layer, forms a unique "ion trapping interface" with metallic VO2. The first coating layer, through the localized electric field effect generated by its atomic vacancy defects and chemisorption sites, can strongly trap Li attempting to cross it. + This "fixes" the lithium ions onto the VO2 surface, forming a dynamic ion migration barrier. This significantly increases the difficulty of lithium ion transport across the separator, essentially creating a low-resistance "soft short-circuit" resistor located inside the separator between the positive and negative electrodes. Before a dangerous concentrated thermal runaway occurs, the energy is proactively and preemptively "discharged," achieving electronic shutdown of the lithium-ion battery.

[0029] Specifically, when the temperature is <65℃, Li + Through the electrolyte passing through the membrane, when Li + When encountering VO2 nanowires encapsulated by a first coating layer (such as h-BN), they flow rapidly along the surface of the first coating layer with almost no retention; at this time, the ion channels of the separator are unobstructed, low-resistance channels, allowing the battery to operate normally and store energy; when the temperature ≥ 65℃, VO2 transforms into a metallic state, affecting Li + It possesses extremely strong adhesion and adsorption forces; moreover, the properties of the interface between h-BN and metallic VO2 have undergone a fundamental change; it is no longer a simple slide, but has become a "beast trap"-like interface; Li attempting to cross the membrane... + Once it gets close to this interface, it will be strongly captured and "stick" to the VO2 surface. Li + Constantly captured and locally accumulated on the VO2 surface, it becomes almost impossible to cross. This instantly establishes a dynamic, extremely high barrier to ion migration within the membrane, preventing the normal ion flow (Li) from reaching the surface. + The flow was almost completely blocked.

[0030] In the above technical solution, the first coating layer of the diaphragm can not only isolate VO2 from direct contact with the electrolyte and prevent side reactions, but it is also an excellent electronic insulator.

[0031] In the above technical solution, the separator uses a dual strategy of "electron discharge (VO2-based composite material is used for separator coating) + ion blocking" to ensure that the battery can be quickly, completely and permanently "shut down" in the early stage of thermal runaway, providing a safety that far exceeds that of a single mechanism (such as traditional PTC or simple pore blocking).

[0032] In an embodiment of the present invention, at least a portion of the surface of the first coating layer is coated with a second coating layer, the second coating layer material being polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether). Polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether) provides ionic conductivity and mechanical toughness at room temperature; the epoxy groups of the block side chains of poly(4-vinylbenzyl glycidyl ether) are stable at room temperature, but under thermal abuse conditions (100°C and above), they can undergo a rapid ring-opening-fluorination-crosslinking synergistic reaction with HF generated from the decomposition of LiPF6, causing the polymer coating to undergo a violent and irreversible volume expansion (up to 300%-500% of its original volume) in a short time, completely blocking the micropores of the base film and the pores of the coating itself like a "cork," thus achieving ion thermal cutoff of the lithium battery. The concerted reaction between epoxy groups and HF is essentially an HF-triggered "living" cationic / ring-opening polymerization of epoxy groups. The HF produced by thermal decomposition acts as a strong protic acid, attacking the oxygen atom of the epoxy group on the P(VBGE) side chain, protonating it, and initiating a ring-opening reaction. The active carbon center produced by ring opening can be converted by fluoride ions (F) in the system. - (From the dissociation or subsequent decomposition of HF) nucleophilic attack, forming a stable CF bond. Simultaneously, the newly formed hydroxyl (-OH) or oxonium (-O) ions... - This substance can act as a new nucleophile to attack another epoxy group, initiating its ring-opening and thus beginning the ether bond (-COC-) linkage process. It transforms soluble / porous linear polymers into insoluble, dense, highly cross-linked fluorinated polyether three-dimensional gels in an extremely short time. The introduced polar hydroxyl groups and the large fluorine atoms generate significant steric hindrance and polar repulsion, forcibly expanding the molecular chain backbone and causing volume expansion. This process leads to a significant blockage of membrane porosity and a sharp decrease in ionic conductivity to near-insulation, achieving a direct, rapid, and irreversible "ionothermal cutoff" from microscopic chemical changes to macroscopic safety functions. Simultaneously, poly(ethylene oxide)-block-poly(4-vinylbenzyl glycidyl ether) can also act as a binder to achieve strong adhesion between nanowires and the base film, eliminating the need for additional PVDF binders.

[0033] In this embodiment of the invention, the aspect ratio of the metal-doped vanadium dioxide nanowires is (50-200):1. The nanowire structure can provide a high specific surface area (>50 m² / g), enhancing contact with the electrolyte; the aspect ratio of 50-200:1 can ensure the formation of a percolation network in the coating, enabling rapid response during phase transitions; exemplary, the aspect ratio of the metal-doped vanadium dioxide nanowires is 50:1, 70:1, 90:1, 100:1, 120:1, 150:1, 180:1, 200:1, etc.

[0034] In this embodiment of the invention, the thickness of the first coating layer is 2-5 nm; the thickness of the second coating layer is 2-5 nm. The in-plane thermal conductivity of the h-BN layer of the first coating layer is >400 W / (m·K), and that of Al2O3 is about 30 W / (m·K), which can quickly and uniformly disperse local hotspot heat and avoid "hotspot concentration"; the 2-5 nm second coating layer acts as a mechanical buffer flexible interface, which can absorb the lattice volume change (~1%) during the VO2 phase transition and prevent nanowire breakage; the PEO segment of the second coating layer is rich in ether oxygen bonds (-O-), which interact with Li + The coating forms coordination, provides a lithium-ion conduction pathway, and reduces interfacial impedance. The PEO segment is electrolyte-friendly, while the PVBGE segment (containing benzene rings and epoxy groups) is electrode-friendly / separator-based film, forming an amphiphilic interface that improves electrolyte wettability. The PEO segment softens and melts at 60-80℃, and the coating porosity decreases with increasing temperature, assisting in blocking ion transport. It works synergistically with the VO2 phase transition to form dual thermal protection. For example, the thickness of the first coating layer is 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, etc. For example, the thickness of the second coating layer is 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, etc.

[0035] In this embodiment of the invention, the thickness of the separator coating is 2-6 μm. A coating of 2-6 μm has little impact on the battery energy density and basically does not sacrifice volumetric energy density; for example, the thickness of the separator coating is 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, etc.

[0036] In this embodiment of the invention, the base film is a polyolefin film with a thickness of 5-8 μm. Exemplarily, the thickness of the base film is 5 μm, 5.5 μm, 6 μm, 6.7 μm, 7 μm, 7.5 μm, 8 μm, etc. A base film thickness of 5-8 μm can shorten the lithium-ion migration distance, reduce the separator impedance, and effectively improve the battery rate performance and energy density; at the same time, the thinner polyolefin film has excellent flexibility and can stably support the coating.

[0037] Methods for preparing diaphragms On the other hand, the present invention also provides a method for preparing a diaphragm, comprising the following steps: S1. Mix the metal source, vanadium source, and reducing agent, then carry out a hydrothermal reaction. After washing and drying, calcine to obtain the chemical formula M. x V 1-x Metal-doped vanadium dioxide nanowires of O2, wherein x is 0.03-0.05 and M is selected from at least one of tungsten, molybdenum and niobium; A first coating layer material is deposited on the surface of the metal-doped vanadium dioxide nanowire to obtain metal-doped vanadium dioxide nanowire with the first coating layer; the first coating layer material is selected from at least one of hexagonal boron nitride, aluminum oxide, and silicon dioxide. S2. PEO-thiocarbonate is pre-activated with an initiator, and then hydrothermally reacted with VBGE monomer to obtain poly(4-vinylbenzyl glycidyl ether). S3. Mix the metal-doped vanadium dioxide nanowires with the first coating layer obtained in step S1 with the polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether) obtained in step S2 to form a slurry. Coat the slurry on at least one surface of the base membrane to obtain the composite membrane. The execution order of steps S1 and S2 is not important.

[0038] In the above technical solution, the first coating layer material is coated on the surface of VO2 nanowires by atomic layer deposition, which has the advantages of uniform coating and precise controllable thickness. The synthesis process of PEO-thiocarbonate pre-activation and re-initiation of VBGE polymerization can prepare block copolymers with more regular structures and more stable epoxy side group content.

[0039] In an embodiment of the present invention, in step S1, the vanadium source includes at least one of ammonium metavanadate, vanadium pentoxide, sodium vanadate, vanadium trichloride, and vanadium oxysulfate.

[0040] In an embodiment of the present invention, in step S1, the metal source is a tungsten source, and the tungsten source includes at least one of ammonium metatungstate, ammonium paratungstate, sodium tungstate, and potassium tungstate.

[0041] In an embodiment of the present invention, in step S1, the reducing agent includes at least one of oxalic acid, urea, ascorbic acid, and hydrazine hydrate.

[0042] In this embodiment of the invention, in step S1, the molar ratio of the metal source and the vanadium source satisfies the following condition: the molar ratio of the metal element to the vanadium element is (3-5): 100. For example, the molar ratio of the metal element to the vanadium element is 3:100, 3.5:100, 4:100, 4.5:100, 5:100, etc.

[0043] In this embodiment of the invention, in step S1, the molar ratio of the reducing agent to vanadium in the vanadium source is (1.5-2.5):1. Exemplarily, the molar ratio of the reducing agent to vanadium in the vanadium source is 1.5:1, 1.7:1, 1.9:1, 2.0:1, 2.1:1, 2.3:1, 2.5:1, etc. When the molar ratio of the reducing agent to vanadium in the vanadium source is within the above range, it can provide sufficient reducing components to ensure that high-valence vanadium is fully reduced to generate the target product, reducing the formation of low-valence or high-valence vanadium impurities; it can also avoid excessive reduction and grain agglomeration distortion caused by excessive reducing agent, which is beneficial for obtaining one-dimensional nanowires with regular morphology and suitable aspect ratio.

[0044] In this embodiment of the invention, in step S1, the hydrothermal reaction specifically involves a reaction time of 48-72 hours at 180-240°C. These hydrothermal reaction conditions facilitate uniform doping of metal ions into the crystal lattice, enabling more precise control of the doping amount, ensuring the crystal grows into nanowires with a suitable aspect ratio, and producing fewer impurities in the product, thereby ensuring stable membrane performance.

[0045] In an embodiment of the present invention, step S1, specifically, involves heating to 500-600°C at a rate of 2-5°C / min under an inert atmosphere and holding at that temperature for 2-4 hours.

[0046] In this embodiment of the invention, in step S1, the first coating layer material is hexagonal boron nitride, and the mass ratio of the first coating layer to the metal-doped vanadium dioxide nanowires is (5-30):(70-95). When the proportion of h-BN is within the above range, the coating layer can form a three-dimensional heat conduction network, which can quickly and uniformly disperse the local Joule heat (in the metallic state) generated by the VO2 phase transition, avoiding the runaway positive feedback of "hot spot-phase transition-heating". If it is too low, it will lead to discontinuous heat conduction path; if it is too high, the thermal conductivity will be saturated but the VO2 functional phase will be excessively diluted. For example, the mass ratio of the first coating layer to the metal-doped vanadium dioxide nanowires is 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, etc.

[0047] In this embodiment of the invention, in step S1, the atomic layer deposition temperature is 150-200℃, and the atomic layer deposition cycle number is 40-100 times. A suitable temperature can prevent high-temperature damage to the crystal structure and phase transition properties of vanadium dioxide, and a suitable number of cycles can precisely control the coating layer thickness, allowing boron nitride and other coating layers to be uniformly and densely coated on the nanowire surface.

[0048] In this embodiment of the invention, in step S2, the pre-activation reaction refers to a stirring reaction at 70-100°C for 6-10 hours. A suitable temperature can fully activate the PEO-thiocarbonate end groups without causing macromolecular degradation, and sufficient reaction time ensures a stable number of activated sites, which is beneficial for the subsequent uniform initiation of VBGE block polymerization, resulting in a well-structured product with stable epoxy content.

[0049] In an embodiment of the present invention, in step S2, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.

[0050] In this embodiment of the invention, in step S2, the molar ratio of PEO-thiocarbonate to the initiator is 1:(0.15-0.25). Exemplarily, the molar ratio of PEO-thiocarbonate to the initiator is 1:0.15, 1:0.18, 1:0.20, 1:0.22, 1:0.23, 1:0.25, etc. When the molar ratio of PEO-thiocarbonate to the initiator is within the above range, the terminal thiocarbonate groups of the macromolecule can be fully activated, resulting in a more regular block structure and a more stable epoxy content. This avoids both excessive initiator causing monomer homopolymerization and insufficient activation leading to low polymerization, resulting in a more balanced block copolymer in terms of adhesive properties and thermally responsive closed-cell properties.

[0051] In this embodiment of the invention, in step S2, the molar ratio of PEO-thiocarbonate to VBGE monomer is 1:50-1:100. When the molar ratio of PEO-thiocarbonate to VBGE monomer is higher than 1:50, due to the excessively high proportion of PEO and the excessively short PVBGE chain segments, the interfacial anchoring function is insufficient, and the coating is prone to detachment from the h-BN surface; when it is lower than 1:100, the proportion of PEO is lower than the percolation threshold (~8%), the lithium ion conduction channels are broken, and the interfacial resistance of the coating increases sharply; for example, the molar ratio of PEO-thiocarbonate to VBGE monomer is 1:50, 1:60, 1:65, 1:70, 1:80, 1:90, 1:100, etc.

[0052] In this embodiment of the invention, in step S2, the hydrothermal reaction specifically involves reacting at 60-100°C for 18-36 hours under an inert atmosphere. The inert atmosphere isolates oxygen, preventing the deactivation of macromolecular free radicals and avoiding thermal damage to the epoxy groups of the VBGE monomer. Suitable temperature and sufficient reaction time enable stable block polymerization, resulting in a more regular molecular structure and higher epoxy side group retention rate, thereby ensuring excellent resin performance.

[0053] In an embodiment of the present invention, in step S3, the mass ratio of the metal-doped vanadium dioxide nanowires with the first coating layer to the polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether) is (70~90):20. Exemplarily, the mass ratio of the metal-doped vanadium dioxide nanowires with the first coating layer to the polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether) is 70:20, 75:20, 80:20, 82:20, 88:20, 90:20, etc. When there is an excessive amount of vanadium dioxide nanowires doped with metal, the nanowire surface is exposed, causing VO2 to come into direct contact with the electrolyte, which may trigger continuous side reactions, consume active lithium, and affect cycle life. When there is an excessive amount of polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether), ions need to pass through a thicker insulating polymer layer to reach the VO2 surface, increasing resistance. Excessive polymer itself can clog numerous pores, potentially causing the ionic conductivity at room temperature to decrease due to increased tortuosity. A suitable mass ratio is necessary to achieve excellent membrane performance.

[0054] In this embodiment of the invention, the mixing specifically involves stirring at a speed of 1500-2500 rpm for 1.5-2.5 hours, followed by ultrasonic treatment for 25-35 minutes.

[0055] Lithium-ion batteries In another aspect, the present invention also provides a lithium-ion battery comprising the separator as described above; and / or a separator prepared according to the separator preparation method described above.

[0056] In embodiments of the present invention, the lithium-ion battery further includes a positive electrode, a negative electrode, and an electrolyte. A separator is disposed between the positive and negative electrode, and the electrolyte fills the pores of the separator and wets the positive and negative electrode. During battery charging and discharging, active ions repeatedly insert and extract between the positive and negative electrode; the electrolyte acts as a conductor of ions between the positive and negative electrode. The present invention does not impose any particular limitations on the positive electrode, negative electrode, and electrolyte, as long as they achieve the purpose of this application.

[0057] The present invention will be further illustrated below with reference to the embodiments: Example 1 A method for preparing a lithium-ion battery includes the following steps: 1. Preparation of negative electrode sheet: The prepared negative electrode active material, conductive agent (conductive carbon black) and binder (CMC) are mixed in a mass ratio of 75:2:23 to obtain a mixed material. The mixed material is thoroughly stirred at high speed in deionized water to obtain a negative electrode slurry. The negative electrode slurry is coated on conventional copper foil, and after drying and pressing, a negative electrode sheet is obtained.

[0058] 2. Preparation of positive electrode sheet: The positive active material (lithium iron phosphate material), conductive agent (conductive carbon black) and binder (PVDF) are mixed in a mass ratio of 93:5:2 to obtain a mixed material. The mixed material is thoroughly stirred at high speed in NMP to obtain a positive electrode slurry. The positive electrode slurry is coated on conventional aluminum foil, dried and pressed to obtain a positive electrode sheet.

[0059] 3. Preparation of the diaphragm: (1) Preparation of tungsten-doped vanadium dioxide nanowires 8g of ammonium metavanadate and ammonium metatungstate were weighed according to an atomic ratio of W:V of 4:100 and dissolved in 80 ml of deionized water. Oxalic acid was added as a reducing agent and complexing agent, with its molar ratio to vanadium ions controlled at 2:1. The mixture was stirred at 1500 rpm for 2 hours to form a clear blue precursor solution. The precursor solution was transferred to a polytetrafluoroethylene-lined high-pressure reactor, and the reaction temperature was controlled at 200℃ for 60 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The precipitate was washed at least three times each with alternating centrifugation using deionized water and anhydrous ethanol to remove residual ions and organic matter. The precipitate was dried in a vacuum drying oven at 60℃ for 16 hours to obtain precursor powder W. x V₂O₅·nH₂O nanowires, where x is 0.04. The precursor powder was placed in a tube furnace and heated from room temperature to 550°C at a rate of 3°C / min under high-purity argon or vacuum, and held at 550°C for 3 hours to ensure complete conversion to W. y V 1-y O2 phase, y = 0.05. After natural cooling to room temperature, the target product—W-doped VO2 nanowires—was obtained.

[0060] (2) h-BN (hexagonal boron nitride) atomic layer deposition coating The synthesized W-doped VO2 nanowires were uniformly spread on the substrate of the ALD reaction chamber (the mass ratio of h-BN layer to W-doped VO2 nanowires was 10:90). Tris(dimethylamino)borane was used as the boron source, and high-purity ammonia or nitrogen was used as the nitrogen source. The reaction chamber temperature was set to 180°C. A single ALD cycle consisted of the following steps: pulsed B(DMA)3 (tris(dimethylamino)borane): 0.1 seconds, to chemically adsorb precursor molecules onto the VO2 nanowire surface; argon purging: 20 seconds, to remove excess physically adsorbed precursors and byproducts; pulsed NH3: 0.1 seconds (or a short plasma treatment if using plasma nitrogen); argon purging: 20 seconds, to ensure chamber cleanliness. The h-BN thickness was precisely controlled by adjusting the number of ALD cycles, with approximately 0.05 nm growth per cycle. To achieve a 3 nm coating, 60 cycles were required, and finally BN@VO2 nanowires were obtained (W-doped VO2 nanowires were uniformly coated with a 3 nm thick layer of amorphous h-BN).

[0061] (3) Synthesis of PEO-bP(VBGE) diblock copolymer (31) PEO-trithiocarbonate (PEO-CTA) and initiator AIBN (azobisisobutyronitrile) were dissolved in anhydrous acetonitrile. The molar ratio of PEO-thiocarbonate to AIBN was 1:0.2. The mixture was stirred at 80°C for 8 hours to obtain pre-activated PEO-CTA.

[0062] (32) Synthesis of PEO-bP(VBGE) block copolymer The pre-activated PEO-CTA and VBGE monomer (vinyl benzyl glycidyl ether) were dissolved in anhydrous toluene, with the molar ratio of VBGE monomer to PEO-CTA controlled at 80:1. The reaction was carried out at 80°C for 24 hours under argon protection. The reaction solution was then placed in a 0°C ice-water bath to expose it to air to terminate the reaction. The polymer was precipitated in ice-cold methanol and collected by filtration or centrifugation. This precipitation-dissolution process was repeated three times for complete purification. The final product was vacuum dried at 60°C for 30 hours to obtain a white solid PEO-bP(VBGE).

[0063] (4) Preparation and coating of composite diaphragm slurry BN@VO2 core-shell nanowires and PEO-bP (VBGE) in a mass ratio of 80:20 were added to N-methylpyrrolidone (NMP) and stirred at 2000 rpm for 2 hours. The mixture was then sonicated for 30 minutes to form a uniform and stable slurry. This slurry was then uniformly coated on both sides of a 5 μm thick polyolefin (PE) base film (4 μm thick coating on both sides). After drying, the film was wound up to obtain the final functional composite membrane (9 μm).

[0064] 4. Electrolyte: Ethyl carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to form a mixed organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare the electrolyte.

[0065] 5. Lithium-ion battery fabrication: After weighing, the electrode sheets were directly used as the negative electrode of the lithium-ion battery. 2032 coin cells were assembled in an Ar-filled glove box. The assembly sequence from top to bottom was: negative electrode shell, gasket, spacer, lithium sheet, separator, self-supporting electrode sheet, and positive electrode shell. The resulting coin cells were further tested on a charge-discharge tester. The cycle stability of the synthesized composite negative electrode material was tested for 300 cycles at a current density of 100 mA / g.

[0066] Example 2-3 The only difference between Examples 2-3 and Example 1 is that: In step 3, membrane preparation, the W:V atomic ratio in step (1) is set to 3:100 and 5:100 respectively, and the remaining steps are the same as in Example 1.

[0067] Examples 4-5 The only difference between Examples 4-5 and Example 1 is that in step 3, membrane preparation, the mass ratio of h-BN layer to W-doped VO2 nanowire in step (2) is set to 5:95 and 30:70 respectively, and the ALD cycle number and the thickness of h-BN are changed accordingly.

[0068] Examples 6-7 The only difference between Examples 6-7 and Example 1 is that in step 3, membrane preparation, the molar ratio of VBGE monomer to PEO-CTA in step (32) is set to 50:1 and 100:1, respectively.

[0069] Examples 8-9 The only difference between Examples 8-9 and Example 1 is that in step 3, membrane preparation, the thickness of the double-sided coating in step (4) is set to 2 and 6 μm respectively.

[0070] Example 10 The only difference between Example 10 and Example 1 is that in step 3, membrane preparation, step (3) is omitted, that is, PEO-bP(VBGE) block copolymer is not used in membrane preparation; Step (4) is changed to: (4) Preparation and coating of composite diaphragm slurry BN@VO2 core-shell nanowires were added to N-methylpyrrolidone (NMP) and stirred at 2000 rpm for 2 hours using a stirrer. Then, the mixture was ultrasonically treated for 30 minutes to form a uniform and stable slurry. This slurry was then uniformly coated on both sides of a 5 μm thick polyolefin (PE) base film (the coating thickness on both sides was 4 μm). After drying, the film was wound up to obtain the final functional composite membrane (9 μm).

[0071] Example 11 The only difference between Example 11 and Example 1 is that in step 3, membrane preparation, h-BN (hexagonal boron nitride) in step (2) is replaced with aluminum oxide.

[0072] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that: 3. Preparation of the diaphragm: Dissolve PVDF in NMP, add alumina powder at a mass ratio of Al2O3:PVDF = 92:8, stir to form a uniform and stable slurry, coat the slurry onto the PP base film, dry and roll it up to obtain the PP / PVDF / ceramic diaphragm.

[0073] Comparative Example 2 The only difference between Comparative Example 1 and Example 1 is that in step 3, membrane preparation, step (2) is omitted, that is, h-BN is not used to coat W-doped VO2 nanowires; In step (4), the BN@VO2 core-shell nanowires are replaced with W-doped VO2 nanowires.

[0074] Comparative Example 3 The only difference between Comparative Example 1 and Example 1 is that in step 3, membrane preparation, steps (1) and (2) are omitted, that is, BN@VO2 core-shell nanowires are not used in membrane preparation.

[0075] Step (4) is changed to: (4) Preparation and coating of composite diaphragm slurry PEO-bP (VBGE) was added to N-methylpyrrolidone (NMP) and stirred at 2000 rpm for 2 hours using a mixer. Then, it was ultrasonically treated for 30 minutes to form a uniform and stable slurry. This slurry was then uniformly coated on both sides of a 5 μm thick polyolefin (PE) base film (4 μm coating thickness on both sides). After drying, the film was wound up to obtain the final functional composite membrane (9 μm).

[0076] Test example: The lithium-ion batteries prepared in each embodiment and comparative example were subjected to internal resistance testing and separator thermal response testing. The specific test conditions are as follows: (1) Internal resistance test: The internal resistance of the battery is tested at 65℃ and 100℃ using an internal resistance meter; (2) Diaphragm thermal response test: Two sets of diaphragms were set up and treated under the following two heat treatment conditions: ① 65℃ heat treatment: The diaphragm was laid flat in a constant temperature oven and kept at 65℃ for 30 min. It was then removed and placed in a desiccator to cool to room temperature; ② 100℃ heat treatment: The diaphragm was laid flat in a constant temperature oven and kept at 100℃ for 30 min. It was then removed and placed in a desiccator to cool to room temperature. The porosity of the two heat-treated diaphragms was measured using the following methods: The diaphragms were cut into 3.5×3.5 squares, and their length, width, and thickness were measured using a micrometer. The cut diaphragms were weighed (m1) using a balance. The diaphragms were immersed in a petri dish filled with hexadecane solution for 1 hour to allow them to fully absorb the solution. The diaphragms were then placed on clean paper with tweezers, and the solution was pressed out using the paper and a roller. The dried diaphragms were weighed (m2) using a balance. The porosity was calculated using the following formulas: Diaphragm porosity = Absorbed liquid volume (hexadecane) / Diaphragm volume; Absorbed liquid volume = (Diaphragm mass after absorption m2 - Diaphragm mass before absorption m1) / hexadecane density (0.773 g / cm³); Diaphragm volume = Length * Width * Thickness.

[0077] The test results of the lithium-ion batteries prepared in each embodiment and comparative example are shown in Table 1.

[0078] Table 1. Electrical performance test results of each embodiment and comparative example.

[0079] As shown in Table 1, the lithium-ion batteries prepared using Examples 1-11 have a porosity of 8.5-14.9 Ω at 65°C, while those of Comparative Examples 1-3 are 8.4-8.9 Ω, showing little difference. However, at 100°C, the internal resistance of the examples increases sharply to 0.81×10³-1.4×10³ Ω, more than 90 times that at 65°C, while the internal resistance of the comparative examples is only 45-55 Ω at 100°C, only 5-6 times that at room temperature, demonstrating a significant performance difference. This indicates that the separator of the present invention can rapidly block ion transport pathways at high temperatures, with the internal resistance increasing sharply and approaching insulation, thereby avoiding continuous electrochemical reactions and irreversible heat accumulation inside the battery under the risk of thermal runaway. In Example 10, without the use of PEO-bP(VBGE) block copolymer, the performance of the resulting lithium-ion battery is worse than that of Examples 1-9, indicating that the setting of PEO-bP(VBGE) block copolymer has a significant impact on the performance of the separator. In Example 11, the material used for the first coating layer is alumina, which has lower performance compared to h-BN in Example 1.

[0080] The lithium-ion batteries prepared in Examples 1-11 had a membrane porosity of 15%–23% at 65°C. However, at 100°C, the porosity of Examples 1-11 decreased significantly to 4%–12%, with a maximum reduction of 73.3% (Example 1 decreased from 15% to 4%). A large number of effective pores in the membrane were blocked, and the ion transport channels were essentially closed. In contrast, the porosity of Comparative Examples 1-3 only decreased from 40%–45% (at 65°C) to 30%–36% (at 100°C), with a maximum reduction of only 28.6%. A large number of interconnected pores remained, making high-temperature self-locking impossible. This result is consistent with the change in internal resistance, further demonstrating that the expansion of the membrane at high temperatures can effectively block pores, significantly reduce porosity, enhance ion blocking effect, and achieve irreversible thermal protection.

[0081] Comparing Example 1 and Comparative Example 1, it can be seen that the membrane of the present invention exhibits significantly superior thermal turn-off performance compared to ordinary PP / PVDF / ceramic membranes. Comparing Example 1 and Comparative Examples 2 and 3, it can be seen that W-doped VO2 nanowires and h-BN have a significant impact on the membrane's performance. This is mainly because after the vanadium dioxide (VO2) undergoes a phase transition (65°C), the coating of the membrane of the present invention, on the metallic VO2 surface, reacts with Li... + It exhibits unusual adsorption and trapping effects. At this point, the first coating layer, acting as the interface control layer, forms a unique "ion trapping interface" with metallic VO2. The first coating layer, through the localized electric field effect generated by its atomic vacancy defects and chemisorption sites, can strongly trap Li attempting to cross it. + This "fixes" the lithium ions onto the VO2 surface, forming a dynamic ion migration barrier that significantly increases the difficulty of lithium ion transport across the separator. It's equivalent to having a low-resistance "soft short-circuit" resistor connected in parallel between the positive and negative electrodes, located inside the separator. Before a dangerous concentrated thermal runaway occurs, the energy is proactively and prematurely "discharged," achieving electronic shut-off of the lithium-ion battery. Under thermal abuse conditions (100°C and above), the second coating layer can undergo a rapid ring-opening-fluorination-crosslinking synergistic reaction with the HF produced by the decomposition of LiPF6, causing the polymer coating to undergo a violent and irreversible volume expansion (up to 300%-500% of its original volume) in a short time. Like a "cork," it completely blocks the micropores of the base film and the pores of the coating itself, achieving thermal ion shut-off of the lithium battery.

[0082] The content of this invention is not limited to the above examples; a combination of one or more examples can also achieve the purpose of this invention.

[0083] The various embodiments in this specification are described in a progressive manner, with each example focusing on the differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. The methods disclosed in the embodiments are described simply because they correspond to the methods disclosed in the embodiments; relevant parts can be found in the method section.

Claims

1. A diaphragm, characterized in that, The diaphragm includes: A base film and a coating disposed on at least one surface of the base film, the coating comprising: Metal-doped vanadium dioxide nanowires, wherein the chemical formula of the metal-doped vanadium dioxide nanowires is M x V 1-x O2, wherein x is 0.03-0.05; M is selected from at least one of tungsten, molybdenum and niobium; at least a portion of the surface of the metal-doped vanadium dioxide nanowire is further coated with a first coating layer, the first coating layer material being selected from at least one of hexagonal boron nitride, alumina and silicon dioxide.

2. The diaphragm according to claim 1, characterized in that, At least a portion of the surface of the first coating layer is coated with a second coating layer, the second coating layer material being polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether).

3. The diaphragm according to claim 1, characterized in that, The aspect ratio of the metal-doped vanadium dioxide nanowires is (50-200):

1.

4. The diaphragm according to claim 2, characterized in that, The thickness of the first coating layer is 2-5 nm; the thickness of the second coating layer is 2-5 nm.

5. The diaphragm according to claim 1, characterized in that, The thickness of the diaphragm coating is 2-6 μm; And / or, the base film is a polyolefin film with a thickness of 5-8 μm.

6. A method for preparing a diaphragm, characterized in that, Includes the following steps: S1. Mix the metal source, vanadium source, and reducing agent, then carry out a hydrothermal reaction. After washing and drying, calcinate to obtain the chemical formula M. x V 1-x Metal-doped vanadium dioxide nanowires of O2, wherein x is 0.03-0.05 and M is selected from at least one of tungsten, molybdenum and niobium; A first coating layer material is deposited on the surface of the metal-doped vanadium dioxide nanowire to obtain metal-doped vanadium dioxide nanowire with the first coating layer; the first coating layer material is selected from at least one of hexagonal boron nitride, aluminum oxide, and silicon dioxide. S2. PEO-thiocarbonate is pre-activated with an initiator, and then hydrothermally reacted with VBGE monomer to obtain poly(4-vinylbenzyl glycidyl ether). S3. Mix the metal-doped vanadium dioxide nanowires with the first coating layer obtained in step S1 with the polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether) obtained in step S2 to form a slurry. Coat the slurry on at least one surface of the base membrane to obtain the composite membrane. The execution order of steps S1 and S2 is not important.

7. The method for preparing the diaphragm according to claim 6, characterized in that, Step S1 satisfies at least one of the following characteristics: (1) The vanadium source includes at least one of ammonium metavanadate, vanadium pentoxide, sodium vanadate, vanadium trichloride, and vanadium oxysulfate; (2) The metal source is a tungsten source, and the tungsten source includes at least one of ammonium metatungstate, ammonium paratungstate, sodium tungstate, and potassium tungstate; (3) The reducing agent includes at least one of oxalic acid, urea, ascorbic acid, and hydrazine hydrate; (4) The molar ratio of the metal source and the vanadium source satisfies the following: the molar ratio of the metal element to the vanadium element is (3-5): 100; (5) The molar ratio of the reducing agent to the vanadium element in the vanadium source is (1.5-2.5):1; (6) In step S1, the hydrothermal reaction specifically refers to a reaction time of 48-72 hours at 180-240℃; (7) The calcination specifically involves heating to 500-600°C at a rate of 2-5°C / min under an inert atmosphere and holding at that temperature for 2-4 hours. (8) The first coating material is hexagonal boron nitride, and the mass ratio of the first coating to the metal-doped vanadium dioxide nanowire is (5-30):(70-95). (9) The temperature of the atomic layer deposition is 150-200℃ and the number of atomic layer deposition cycles is 40-100.

8. The method for preparing the diaphragm according to claim 6, characterized in that, Step S2 satisfies at least one of the following characteristics: (1) The pre-activation reaction refers to stirring the reaction at 70-100℃ for 6-10 hours; (2) The initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide; (3) The molar ratio of the PEO-thiocarbonate to the initiator is 1:(0.15-0.25). (4) The molar ratio of the PEO-thiocarbonate to the VBGE monomer is 1:50 - 1:100; (5) In step S2, the hydrothermal reaction is specifically carried out at 60-100°C for 18-36 hours under an inert atmosphere.

9. The method for preparing the diaphragm according to claim 6, characterized in that, In step S3, the mass ratio of the metal-doped vanadium dioxide nanowires with the first coating layer to the polyethylene oxide-block-poly(4-vinylbenzyl glycidyl ether) is (70~90):

20. And / or, the mixing specifically involves stirring at a speed of 1500-2500 rpm for 1.5-2.5 hours, followed by ultrasonic treatment for 25-35 minutes.

10. A lithium-ion battery, characterized in that, The membrane includes the membrane as described in any one of claims 1 to 5; and / or the membrane prepared by the method described in any one of claims 6 to 9.